2019
DOI: 10.1080/09593330.2019.1619844
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flow hydrodynamics and pipe material properties on biofilm development within drinking water systems

Abstract: The aim of this study was to investigate the combined impact of flow hydrodynamics and pipe material on biofilm development in drinking water distribution systems (DWDS). Biofilms were formed on four commonly used pipe materials (namely polyvinyl chloride, polypropylene, structured wall high-density polyethylene and solid wall high-density polyethylene) within a series of purpose built flow cell reactors at two different flow regimes. Results indicate that varying amounts of microbial material with different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Studies have shown that, when compared to WDSs with high velocity water flows (>0.3 m/sec), those with low velocity flows have lower hydrodynamic shear forces at the internal surface of their pipes, which leads to growth of thicker, less dense and less stable biofilms [ 41 , 42 , 43 ]. Further to this, low velocity water flows through pipes lead to higher concentrations of antimicrobial-resistant bacteria (ARB) and a higher prevalence of antimicrobial-resistant genes (ARGs), and different microbial community compositions than are found in pipes with higher velocity water flow [ 44 , 45 , 46 ]. Exposure of microbial communities in biofilms to sub-inhibitory antimicrobial concentrations, which is likely in pig building WDSs, especially during lower metaphylactic in-water dosing events conducted over >12 h, could also modulate biofilm matrix composition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, when compared to WDSs with high velocity water flows (>0.3 m/sec), those with low velocity flows have lower hydrodynamic shear forces at the internal surface of their pipes, which leads to growth of thicker, less dense and less stable biofilms [ 41 , 42 , 43 ]. Further to this, low velocity water flows through pipes lead to higher concentrations of antimicrobial-resistant bacteria (ARB) and a higher prevalence of antimicrobial-resistant genes (ARGs), and different microbial community compositions than are found in pipes with higher velocity water flow [ 44 , 45 , 46 ]. Exposure of microbial communities in biofilms to sub-inhibitory antimicrobial concentrations, which is likely in pig building WDSs, especially during lower metaphylactic in-water dosing events conducted over >12 h, could also modulate biofilm matrix composition.…”
Section: Discussionmentioning
confidence: 99%
“…hydraulic parameters on the community was also evident when comparing BF3 and BF4. Biofilms formed in contact with drinking water under lower flow rates have higher biomass, DNA concentration and total number of cells, 45 suggesting that water flowing at a reduced rate at BF4 may have had contact with a similar amount of biomass, and subsequent nitrification, as that at BF3, and supporting similar communities at these locations. The pipe section with BF4 serves fewer consumers and thus while equally distant as BF1 from the DWTP, the water at BF4 likely had contact with the biofilm similar to that at BF3, and supported by the higher TCC in the water at DP2 than DP3.…”
Section: Changes In the Biofilm Community Driven By Nitrificationmentioning
confidence: 86%
“…Most of the research in this area has been devoted to the impact of shear and surface characteristics on biofilm formation, giving less relevance to microbial cell adhesion ( Table 3 ). It was also observed that flow systems, namely modified Robbins devices and rotating biofilm devices, are the main choice to emulate the turbulent flows and high wall shear stresses found in water systems [ 79 , 80 , 81 ]. However, in the last few years, efforts have been made to predict flow conditions in easy-to-handle biofilm platforms like microplates [ 68 , 71 ].…”
Section: Adhesion and Biofilm Studies Performed Under Controlled Hydrodynamicsmentioning
confidence: 99%